(untitled) (Journal of the Bangladesh Agricultural University, 2014)
An experimental small scale desalination system where solar energy as the main heat source was conducted in a remote area of Coxs Bazar district of Bangladesh. In this investigation, the performance of three solar stills with transparent glass cover was studied. Treated sea water was given to the solar still and the quantity of distilled water from three solar stills was measured per day and the effectiveness of the stills was compared. The performance of these stills was checked for 20 days. The different parameters i.e. ambient temperature, Salinity, pH, Unionized NH3, Iron, NO2-N, Chlorine, DO and amount of distilled water were studied and analyzed. The average amount of water produced by the still (1) was 455 ml, still (2) was 394.75ml and still (3) was 339.25 ml. The total amount of water produced by the still (1) was 9100 ml, still (2) was 7895 ml and still (3) was 6785 ml. The average desalinated water were obtained 1.06 liter/m2/day, 0.98 liter/ m2/day and 0.95 liter/ m2/day from still 1, 2 and 3 respectively. DOI: http://dx.doi.org/10.3329/jbau.v11i1.18229 J. Bangladesh Agril. Univ. 11(1): 165-170, 2013